Status, causes and consequences of physicians’ self-perceived professional reputation damage in China: a cross-sectional survey - Sun, Tao (BMC Health Serv Res, 2021)
BACKGROUND: Conflict between physicians and patients is an increasingly serious problem, leading to the disrepute attached to Chinese physicians’ social image and position. This study assesses the status of physicians’ self-perceived professional reputation damage and explains it’s the adverse outcomes including withdrawal behavior and workplace well-being. Moreover, potential causes of Chinese physicians’ disrepute have been outlined. METHODS: Primary data were collected through a cross-sectional online survey of physicians from 10 provinces in China, who were invited to complete an anonymous survey from December 2018 to January 2019. A total of 842 physicians (effective response rate: 92.22%) were recruited as participants. RESULTS: About 83% of the participants self-perceived professional reputation damage from the sense of the public opinion concept. Approach half of participants exhibited the idea of turnover intention (47.3%) and one or more symptoms of burnout (46.4%). About 74.9% of the participants experienced a degree of stress. Additionally, three out of five participants reported low-level subjective well-being. More than 70% of the participants disapproved of their offspring becoming a physician. Four factors leading to physicians’ damaged professional reputations are those addressed: conflict transfer, cognitive bias, improper management, and individual deviance. Stigmatised physicians are more likely to practice high-frequent defensive medicine (β = 0.172, P <0.001), intend to leave the profession (β = 0.240, P <0.001), disapprove of their children becoming physicians (β = 0.332, P<0.001) and yield worse levels of workplace well-being, including high levels of perceived stress (β = 0.214, P <0.001), increasing burnout (β = 0.209, P <0.001), and declining sense of well-being (β = − 0.311, P<0.001). CONCLUSION: Chinese physicians were aware of damaged professional reputations from the sense of the public opinion concept, which contributes to increasing withdrawal behaviors and decreasing workplace well-being—a worsening trend threatening the entire health system. This novel evidence argues a proposal that Chinese health policy-makers and hospital administrators should promote the destigmatization of physicians immediately. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12913-021-06306-6.